Reverse Distraction Cranioplasty for Treatment of Hydrocephalic Megalocephaly. Issue 8 (November 2015) - Saad, Ahmad N.; Kanack, Melissa; McIntyre, Joyce; Levy, Michael; Meltzer, Hal; Cohen, Steven R.
Abstract : Abstract: Macrocephaly resulting from untreated hydrocephalus is a rare but difficult condition to treat. The patient presented is a 6-year-old boy who had progressively increasing head size since birth secondary to untreated hydrocephalus with associated developmental delay. His initial head circumference was 69 cm, and computed tomography scan showed evidence of obstructive hydrocephalus. For the first stage of the procedure, bicoronal and circumferential strip craniectomies were performed, 5 fully open 3.5 mm midface distractors were placed to facilitate vault reduction, and absorbable plates were placed in the frontoorbital region. Neurosurgery also performed an endoscopic third ventriculostomy and placed an external ventricular drain. Reverse distraction was completed over 5 days and tolerated well by the patient. Three months after the first procedure, the distractors were removed and frontoorbital reduction and additional cranial vault reduction and reshaping were performed. At 1 month following this operation he was noted to have excellent forehead contour and dramatic improvement of his macrocephaly with some remaining mid-vault asymmetry. His head circumference was measured at 61.5 cm with bicoronal distance of 39.5 cm. He demonstrated improvement in head control and ability to sit. This patient demonstrates a new technique for reduction cranioplasty involving the use of reverse distraction to facilitate gradual and controlled reduction prior to extensive cranial vault remodeling. The challenges associated with managing hydrocephalus in cranial vault reduction patients are also addressed.